Different Treatment Modality in the Management of Acute Mesenteric Ischemia - Selim, Mohamed (Cureus, 2021)
Mesenteric ischemia (MI) is a reduction in blood flow of the mesenteric vessels resulting in ischemia or infarction if not treated properly. It is difficult to diagnose and it has a high rate of mortality. Moreover, it is managed either by open surgery or endovascular approach. We present a case of a 79-year-old male patient with MI managed initially by thrombolytic therapy with stent through inferior mesenteric artery which has failed. Few days later he presented with the same complaint. He was treated with heparin for five days and discharged in good condition. Six days later, the patient returned to the ED with MI and managed successfully with retrograde right common ilio-mesenteric artery bypass with no complication and made full recovery. Endovascular revascularization is a minimally invasive approach and it is the initial treatment of choice for mesenteric occlusive disease. However, this approach is not always feasible which explains the role for open approach.